Rethinking Poverty : What makes a good society? - Knight, Barry, 1947- (Book collections on Project MUSE., 2017)
Epdf available Open Access under CC-BY-NC licence In our society, a wealthy minority flourish, while around one-fifth experience chronic poverty and many people on middle incomes fear for their futures. Social policy has failed to find answers to these problems and there is now a demand for a new narrative to enable us to escape from the crisis in our society. With the aim of ending poverty, this book argues that we need to start with the society we want, rather than framing poverty as a problem to be solved. It calls for abold forward-looking social policy that addresses continuing aust.